RISK FACTORS OF NON-COMMUNICABLE DISEASES - Al-Anshary, Aisyah Sholeh; Susanti, Nofi; S., Eva Mulyani; Sari, Kurnia Permata; Hera, Salwa Radah (HEARTY, 2024)
Non-communicable diseases (NCDs) continue to be the leading cause of death and disability worldwide. This study investigates the main risk factors for NCDs by systematically reviewing the latest literature and literature studies. The main focus is on the influence of genetic factors, life behavior, socio-economic conditions and environmental factors as the main determinants of this disease. Through critical analysis of multiple data sources, including medical textbooks and peer-reviewed journal articles, this study identified that poor diet, physical inactivity, tobacco use, and exposure to environmental pollutants significantly increase the risk of NCDs. This study also emphasizes the importance of interventions at the policy and individual levels to address these risk factors. It is hoped that the results of this study can become a basis for developing more effective preventive and health promotion strategies in the future.